AB1095 Identifying Under-Recognised, Clinically Significant Co-Morbidities and Assessing Disease Activity in RA Patients. (10th June 2014) - Waller, R.; Williamson, L.; Collins, D.; Price, E.
Abstract : Background: Many patients with RA have under-treated disease and failure to recognise co-morbidities in RA puts our patients at risk of significant increased morbidity and mortality. Complementing the clinical assessment with patient reported outcome measures using a patient completed pre-assessment tool allows a more in-depth assessment. Methods: Pre-clinic, patient reported questionnaires (PRQs) were sent to all patients on our electronic database with a diagnosis of RA. Questions covered gastrointestinal (GI) symptoms, cardiovascular (CVS) symptoms and risk factors, foot symptoms (score out of 10) and anxiety and depression (Hospital Anxiety and Depression Scores (HADS)). All patients were then reviewed clinically, a full history and examination were undertaken and HAQ, DAS and QRISK2 scores were calculated for each patient. Results: 597 questionnaires were sent, 301 (50%) completed and 129 patients were reviewed in clinic. Disease Activity: Mean DAS score 3.04; Mean HAQ score 1.25 Mood: HADS scores: Anxiety score >11 in 41/129 (32%); mean 8. Depression score >11 in 46/129 (36%) mean 9. Cardiovascular risk: 54/129 (42%) had a QRISK2 greater than 20%. 60% agreement in score comparing information from postal questionnaire with clinic. Only 5% of patients assessed as low risk by PRQ were given a high risk score in clinic 19 patients had hypertension and 32 had raised cholesterol at clinic review, which was not picked up by PSQ. Foot symptoms: 89% of patients reported foot symptoms in the week prior to postal questionnaire. Mean score 4/10. Mean score at clinic review 4/10 - correlation co-efficient 0.63. 65/129 (46%) required intervention by a podiatrist. GI symptoms: 75% of patients reported GI symptoms on at least a monthly basis, with 17% reporting daily symptoms by PSQ. No extra symptoms of concern were elicited at clinic review in any patient Conclusions: Pre clinic screening by questionnaire is an efficient, effective and feasible way of identifying co-morbidities and directing treatment. Co-existing conditions can have an important bearing upon treatment success, therefore global health review is important when assessing RA patients for annual review Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3664